CORNEL ȚĂRANU: PROFESSIONAL AND COMPOSITIONAL TRAJECTORY - ŞUTEU, Cristina (Studia Universitatis Babes-Bolyai Musica, 2020)
A plurivalent personality, the master and academician Cornel Țăranu (born in Cluj on June 20, 1934) is a prominent figure in contemporary Romanian and universal music. In this article I presented the professional trajectory in a chronological and logical sequence of events of Cornel Ţăranu’s life, the list of all the doctoral theses supervised, his musicological publications, as well as his musical creation, organized by genres. He distinguished himself as a composer, musicologist, teacher, conductor of the “Ars Nova” ensemble as well as artistic director of the “Cluj Modern” Contemporary Music Festival, currently holding the position of Honorary President. His background is based on an exceptional professional training studying with Sigismund Toduță, Nadia Boulanger, Olivier Messiaen, Karlheinz Stockhausen, György Ligeti. He composed two operas (The Secret of Don Giovanni between 1969-1970 and Orestes and Oedipus between 1999-2001), chamber music, vocal, vocal-symphonic, orchestral, as well as film music. Representing an effigy of the contemporary Romanian music school of composition, Cornel Țăranu has included over 100 works in the patrimony of the national musical culture.